2002
DOI: 10.1046/j.1432-1033.2002.02875.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies on the core and the O‐polysaccharide repeating unit of Pseudomonas aeruginosa immunotype 1 lipopolysaccharide

Abstract: The structure of the lipopolysaccharide (LPS) of Pseudomonas aeruginosa immunotype 1 was studied after mild acid and strong alkaline degradations by MS and NMR spectroscopy. Three types of LPS molecules were found, including those with an unsubstituted glycoform 1 core (A) or an isomeric glycoform 2 core substituted with one O‐polysaccharide repeating unit (B) or with a long‐chain O‐polysaccharide. Therefore, of two core glycoforms, only glycoform 2 accepts the O‐polysaccharide. In the structures A and B, Kdo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 20 publications
3
67
0
Order By: Relevance
“…Many of the sugars identified in our carbohydrate analysis correspond to sugars found in P. aeruginosa LPS (e.g., KDO, N-acetyl sugars, glucose, etc). Both rhamnose and glucose are core monosaccharides, whereas rhamnose is also an important component of A-band LPS (44,45). The presence of 2-linked and 3-linked rhamnose sugars further supports that our EPS samples contain LPS sugars (Table 4).…”
Section: Discussionsupporting
confidence: 62%
“…Many of the sugars identified in our carbohydrate analysis correspond to sugars found in P. aeruginosa LPS (e.g., KDO, N-acetyl sugars, glucose, etc). Both rhamnose and glucose are core monosaccharides, whereas rhamnose is also an important component of A-band LPS (44,45). The presence of 2-linked and 3-linked rhamnose sugars further supports that our EPS samples contain LPS sugars (Table 4).…”
Section: Discussionsupporting
confidence: 62%
“…Bound to the second heptose residue, Hep II , is a 7-O-carbamyl group (Beckmann et al, 1995), which is found in the LPS of other types of pseudomonads (Knirel et al, 1996). The 2 heptose residues are often phosphorylated at positions 2 and 4 of Hep I and position 6 of Hep II (Bystrova et al, 2002;Knirel et al, 2001;Sadovskaya et al, 2000). Phosphate substituents can be mono-, di-or even tri-phosphates, with most analyzed P. aeruginosa LPS having some triphosphate, which, to date, has only been detected in the LPS of this bacterial species.…”
Section: P Aeruginosa Lps Structurementioning
confidence: 99%
“…The outer core of the P. aeruginosa LPS is usually synthesized as 2 different isoforms or glycoforms by an individual strain (Bystrova et al, 2002(Bystrova et al, ,2006Sadovskaya et al, 2000). Both outer-core glycoforms contain an N-alanylated galactosamine residue, 3 D-glucose residues, and one L-rhamnose residue the position of which differs in the 2 glycoforms (Fig.…”
Section: P Aeruginosa Lps Structurementioning
confidence: 99%
“…7-O-carbamyl group is bound to the second heptose residue, HepII [22], and is also found in the LPS of other types of pseudomonads [23]. The two heptose residues are often phosphorylated at positions 2 and 4 of HepI and position 6 of HepII [24][25][26].Phosphate substituents are mainly mono-and di-phosphates, however, tri-phosphates are also commonly found, which is unique to P. aeruginosa. Phosphorylation of the P. aeruginosa LPS inner core is necessary for the bacterial survival; a mutation in the waaP gene that phosphorylates position 4 of the HepI groups is lethal for the organism [27].…”
mentioning
confidence: 99%
“…O-antigens are built of repeating units of oligosaccharides, the chemical structures of which are strain-specific. The outer cores of the P. aeruginosa LPS are usually synthesized as two different isoforms or glycoforms by individual strains [20,24,26]. Both isoforms contain an N-alanylated galactosamine residue, three Dglucose residues and one L-rhamnose residue, the specific position of which depends on the isoform (Fig.…”
mentioning
confidence: 99%